2003
DOI: 10.1084/jem.20030299
|View full text |Cite
|
Sign up to set email alerts
|

IL-1 Plays an Important Role in Lipid Metabolism by Regulating Insulin Levels under Physiological Conditions

Abstract: IL-1 is a proinflammatory cytokine that plays important roles in inflammation. However, the role of this cytokine under physiological conditions is not known completely. In this paper, we analyzed the role of IL-1 in maintaining body weight because IL-1 receptor antagonist–deficient (IL-1Ra−/−) mice, in which excess IL-1 signaling may be induced, show a lean phenotype. Body fat accumulation was impaired in IL-1Ra−/− mice, but feeding behavior, expression of hypothalamic factors involved in feeding control, ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
151
3
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 197 publications
(168 citation statements)
references
References 68 publications
(61 reference statements)
13
151
3
1
Order By: Relevance
“…In this report, we analysed Il1ra −/− mice on a HFD and found that they are resistant to HFD-induced obesity, which is consistent with previous reports [9,10]. The SNS is activated in these mice, resulting in the activation of BAT and emergence of multilocular BAT-like cells in WAT depots.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In this report, we analysed Il1ra −/− mice on a HFD and found that they are resistant to HFD-induced obesity, which is consistent with previous reports [9,10]. The SNS is activated in these mice, resulting in the activation of BAT and emergence of multilocular BAT-like cells in WAT depots.…”
Section: Discussionsupporting
confidence: 90%
“…The expression level of Ucp1 mRNA in the inguinal WAT of Il1ra −/− mice was significantly higher than in WT mice (Fig. 3a), whereas levels of Ucp1 in epididymal WAT and soleus muscles were not significantly different (data not shown) [9]. We also found that the expression of genes encoding rate-limiting enzymes of mitochondrial fatty acid oxidation, such as Mcad (also known as Acadm) and Mcpt1, was increased in inguinal WAT from Il1ra −/− mice, suggesting that the increased level of oxidation in the inguinal WAT of Il1ra −/− mice probably resulted from an increase in the number of metabolically active mitochondria.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations